Analisis Kinerja Pertumbuhan Ikan Patin (Pangasius Sp.) pada Sistem Budidaya dengan Kolam Terpal - Rosmawati Gea; Rindarianti Zai; Fakta Perjuangan Lombu; Dara Dwista Telaumbanua; Rosevelt Cerdas Lase; Agnes Juwita Dawolo; Ratna Dewi Zebua (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2025)
This study aims to analyze the growth performance of catfish (Pangasius sp.) cultivated in a tarpaulin pond system. Patin fish farming is one of the leading fisheries subsectors in Indonesia due to its high market demand and high nutritional content. The tarpaulin pond system was chosen because it offers efficiency in water quality management and disease risk reduction. This study was conducted in Gunungsitoli in December 2024, using an experimental method that included measuring fish length and weight during the rearing period. The results showed that water quality, including temperature (26-28°C), pH (6.5-7.5), and dissolved oxygen level (5 mg/L), played an important role in determining the fish survival rate, which reached 90%. Feeding strategies with a combination of artificial and natural feeds (silkworms, Artemia) have been shown to significantly improve fish growth. The main challenges in this aquaculture include water quality fluctuations, fry adaptation, and disease management, which can be overcome with aeration technology, probiotics, and natural immunostimulants. With the right innovations, the tarpaulin pond system proves to be an efficient and sustainable farming method in supporting catfish productivity.